AINIDIU, CANDI, HELPMI: ICTs of a personal experience - Jadán-Guerrero, Janio (2012)
This paper presents an overall picture of the current situation of children with special educational needs (SEN) in Ecuador and the development of software adapted to our environment as response to a personal experience of the author. © 2012 IEEE.